Theory of Planned Behavior (TPB) and Hypertension Prevention - Asep Sukohar; Suharmanto (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Hypertension is still high in morbidity and mortality in the world and Indonesia. The numberof people with hypertension is increasing every year. Aim: This review summarizes the Theory of PlannedBehavior (TPB) in the prevention of hypertension. Materials and Method: The literature search wascarried out in February 2021 on the PubMed database using the keywords “theory of planned behavior”,“prevention” and “hypertension”. The articles used are the articles of the last 10 years (from 2011-2020).The search found 30 articles and 8 articles that fit the criteria were discussed. The number of respondents inthis study was between 25-306 with a total of 1,331 people. The questionnaire was used in the study for datacollection. Results: Respondents are students, adolescents, residents, and communities from Iran, Thailand,and USA. TPB provides benefits in an educational program for people who are at risk of hypertension.Subjective norms, perceived behavioral control (PBC), intention increased hypertension prevention.Conclusion: TPB-based interventions are effective for hypertension prevention. All TPB constructs playan important role in hypertension prevention. The TPB model is still feasible and relevant for assessinghypertension prevention behavior.